2022
DOI: 10.1371/journal.pgph.0000985
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to health services through health reform in Lesotho: Progress made towards achieving Universal Health Coverage

Abstract: In 2014 the Kingdom of Lesotho, in conjunction with Partners In Health, launched a National Health Reform with three components: 1) improved supply-side inputs based on disease burden in the catchment area of each of 70 public primary care clinics, 2) decentralization of health managerial capacity to the district level, and 3) demand-side interventions including paid village health workers. We assessed changes in the quarterly average of quality metrics from pre-National Health Reform in 2013 to 2017, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In a recent LPHCR study conducted by Ndayizigiye et al, the authors found that the quarterly average number of women who attended their first ANC visit rose from 1877 (SD ±263) pre-LPHCR to 2729 (SD ±287) in the last year of the intervention (LPHCR/TT). 15 Observed data completion improvement during the LPHCR/TT period and during the LPHCR highlights the synergy between different national-level initiatives aimed at improving population health outcomes. Mixed-effects regression analysis showed that the association was not confounded by health facility type and differences by district.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent LPHCR study conducted by Ndayizigiye et al, the authors found that the quarterly average number of women who attended their first ANC visit rose from 1877 (SD ±263) pre-LPHCR to 2729 (SD ±287) in the last year of the intervention (LPHCR/TT). 15 Observed data completion improvement during the LPHCR/TT period and during the LPHCR highlights the synergy between different national-level initiatives aimed at improving population health outcomes. Mixed-effects regression analysis showed that the association was not confounded by health facility type and differences by district.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Lesotho was behind on key millennium development goals aimed at improvement of maternal and child health outcomes. 15 To address gaps and to strengthen primary care, the Government of Lesotho, in partnership with Partners In Health, launched the first phase of the Lesotho National Primary Health Care Reform (LPHCR)-a pilot-in April 2014, in four districts: Berea, Leribe, Butha Buthe and Mohale's Hoek. 15 The three main objectives of the LPHCR were to improve service delivery, strengthen health system management and empower professional village health workers.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Lesotho has a population just over 2 million and is classi ed as a lower-middle-income country 16 . Health services have traditionally been geared towards the control of infectious diseases and infant and maternal mortality [17][18][19] . Despite a signi cant prevalence of hypertension and diabetes in the country 20 , up-to-date data about awareness, treatment and control of hypertension and diabetes is scarcely available and is not routinely used to guide programmatic interventions.…”
Section: Introductionmentioning
confidence: 99%